Microplastics as a threat to coral reef environments: Detection of phthalate esters in neuston and scleractinian corals from the Faafu Atoll, Maldives. (May 2019) - Saliu, Francesco; Montano, Simone; Leoni, Barbara; Lasagni, Marina; Galli, Paolo
Abstract: The impact of microplastics (MPs) on reef-building corals are still largely unknown. The scientific literature provides evidence from lab feeding trials that coral may ingest MPs. Several adverse effects, i.e., necrosis and bleaching, have also been highlighted. However, field studies are limited. Here, we investigated for the first time the possible correlation between MP seawater contamination and the presence of phthalic acid esters (PAEs), a class of MP-associated contaminants, in scleractinian corals. The survey was carried out in a remote coral reef atoll in the Indian Ocean located in the Maldivian archipelago, considered as a case study. MPs and PAEs were monitored in subsurface neustonic tow samples and scleractinian corals across twelve sampling sites. The results showed widespread MP contamination and the presence of appreciable levels of PAEs in the scleractinian corals sampled inside the atoll rim near an inhabited island, which correlated with the highest MP concentration. Highlights: Microplastic and phthalates contamination was investigated across the Faafu Atoll, Maldives. Analysis were carried out on subsurface water and scleractinian corals. Significant differences were observed among the subsurface water samples from the inside and outside of the atoll rim. Highest phthalates concentration was observed in the scleractinian corals sampled near inhabited island. Data represent an on-site evidence of the chemical interaction of microplastic with scleractinian corals.